Forging Strong and Purposeful Husband-and-Wife Relations: An Africana Womanist Study of Love in Kireni Zulu’s Songs “Zveimba” and “Ndichakuvaraidza” - Charles Tembo; Allan Maganga (Unisa Press, 2023)
In many African societies, the relationship between a husband and a wife is a matter of interest to many in the grand scheme of things. Mutual investment between wife and husband is celebrated for the immense value that goes with it, while lack thereof is debilitating. This article comparatively engages Kireni Zulu’s songs “Zveimba” (Marriage issues) and “Ndichakuvaraidza” (I will comfort you). Mutual cooperation between marriage partners is extolled as the magic formula to more humane life conditions born out of love, peace and harmony in the family. On the contrary, a schism is castigated as an impediment to human progress. Critical engagements in this paper are decidedly Africana womanist.